2013
DOI: 10.1002/oby.20603
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal exposure to persistent organic pollutants and rapid weight gain and overweight in infancy

Abstract: Objective: To examine the effects of prenatal exposure to persistent organic pollutants (POPs) on rapid growth in the first 6 months of life and overweight at 14 months of age. Design and Methods: In a Spanish birth cohort study, the POPs dichlorodiphenyldichloroethylene (DDE), hexachlorobenzene (HCB), and polychlorinated biphenyls (PCBs-congeners 153, 138, 180) were measured in maternal serum collected in the first trimester of pregnancy during [2003][2004][2005][2006][2007][2008]. Rapid growth was defined as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
107
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(120 citation statements)
references
References 40 publications
10
107
0
Order By: Relevance
“…A similar result has been reported for children aged one to three years prenatally exposed to PCB (Verhulst et al, 2009). Most other studies have attributed an increased BMI of the child to an increase in weight or weight gain (Mendez et al, 2011;Valvi et al, 2014), without considering height. Studies considering height and weight growth separately have reported mixed results concerning their association with prenatal exposure to DDE (Garced et al, 2012;Gladen et al, 2000;Ribas-Fitó et al, 2006) or with prenatal exposure to PCBs (Gladen et al, 2000;Hertz-Picciotto et al, 2005;Patandin et al, 1998;Ribas-Fitó et al, 2006).…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…A similar result has been reported for children aged one to three years prenatally exposed to PCB (Verhulst et al, 2009). Most other studies have attributed an increased BMI of the child to an increase in weight or weight gain (Mendez et al, 2011;Valvi et al, 2014), without considering height. Studies considering height and weight growth separately have reported mixed results concerning their association with prenatal exposure to DDE (Garced et al, 2012;Gladen et al, 2000;Ribas-Fitó et al, 2006) or with prenatal exposure to PCBs (Gladen et al, 2000;Hertz-Picciotto et al, 2005;Patandin et al, 1998;Ribas-Fitó et al, 2006).…”
Section: Discussionsupporting
confidence: 76%
“…Higher prenatal exposure was associated with a higher BMI at three months in boys and with a higher BMI and a lower height and height growth velocity at 8 and 18 months in girls. Similar studies investigating other organochlorine chemicals with hormonal activities have reported an increase in BMI or risk of overweight associated with prenatal DDT/ DDE exposure at different ages (from 14 months to 6.5 years) (Mendez et al, 2011;Valvi et al, 2014Valvi et al, , 2012Verhulst et al, 2009). However, one study reported a decrease in BMI (de Cock et al, 2014a(de Cock et al, , 2014b and several reported an absence of association (Cupul-Uicab et al, 2013;Garced et al, 2012;Gladen et al, 2004;Warner et al, 2013).…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…pesticides, flame retardants, plasticizers or dyes may have adverse effects on human health, as revealed by numerous epidemiological studies (Gascon et al, 2014(Gascon et al, , 2015Valvi et al, 2014;Shim et al, 2009;Dahlgren et al, 2003). There is a great number of data in the literature describing induction of xenobiotics-metabolizing human cytochromes P450 by food contaminants and environmental pollutants (Novotna and Dvorak, 2014;Vrzal et al, 2013;Kamenickova et al, 2013;Ayed-Boussema et al, 2012;Lee et al, 2006;Nekvindova et al, 2006).…”
Section: Introductionmentioning
confidence: 97%
“…103 Exposure increases weight gain in animals, 104 and causes rapid growth in the first year of life in humans. 105 The mechanism by which POPs act as obesogens is unknown, but may be mediated through steroid receptors. 104 POPs are known neurotoxins.…”
Section: Persistent Organic Pollutantsmentioning
confidence: 99%